PENGARUH KECERDASAN SPIRITUAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN - Wati, Rahma; Hasyim, Budi (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to analyze the influence of spiritual intelligence and emotional intelligence on employee performance. Employee performance is a crucial factor in determining organizational success, influenced not only by technical capabilities but also by psychological aspects and individual values. This study employed a quantitative approach with a causal associative method. The population in this study was all private sector employees located in Tarakan City, with a sample of 150 respondents determined using a probability sampling technique with simple random sampling. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression analysis with the aid of statistical software. The results showed that spiritual intelligence had a positive and significant effect on employee performance. Furthermore, emotional intelligence also had a positive and significant effect on employee performance. Simultaneously, spiritual intelligence and emotional intelligence had a positive and significant effect on employee performance. These findings suggest that human resource development oriented toward strengthening spiritual intelligence and emotional intelligence can be an effective strategy for improving employee performance. This research is expected to provide theoretical contributions to the development of human resource management science and provide practical applications for organizations in designing more holistic employee development programs.